Cretaceous-Paleogene Low Temperature History of the Southwestern Province, Svalbard, Revealed by (U-Th)/He Thermochronometry: Implications for High Arctic Tectonism - Barnes, Christopher (Université d'Ottawa / University of Ottawa, 2016)
The High Arctic has been a complex region of collisional and extensional tectonism through the Mesozoic and Cenozoic. Svalbard, the sub-aerial exposure of the northwestern Barents Shelf, is an excellent natural laboratory investigating for High Arctic tectonism. Using apatite and zircon (U-Th)/He low-temperature thermochronometry combined with geological constraints, we resolve Cretaceous through Paleogene time-temperature histories for four regions of the Southwestern Province. Our results indicate a temperature gradient from south to north of ~185°C to >200°C, respectively, as a consequence of sedimentary burial and elevated geothermal gradient ( 45°C/km) from High Arctic Large Igneous Province activity. Late Cretaceous cooling affected all regions during regional exhumation related to initial rifting in the Eurasian Basin. During Eurekan tectonism: 1) our models indicate a heating event (55-47 Ma) characterized by overthrusting and a lack of erosion of the West Spitsbergen Fold-and-Thrust Belt, with Central Basin sediments derived from northern Greenland, followed by 2) a subsequent cooling event (47-34 Ma) corresponding to a shift in tectonic regime from compression to dextral strike-slip kinematics; exhumation of the WSFTB coincided with strikeslip tectonics.
Keywords: (U-Th)/He thermochronology; Southwestern Province; West Spitsbergen Fold-and-Thrust Belt; Wandel Hav Mobile Belt